BENTUK-BENTUK TES DAN KARAKTERISTIKNYA DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Hanik Rahmawati Solikhah; Anny Izzatul Mujahidah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Tests are one of the primary instruments in educational evaluation used to measure students’ learning achievement. The selection of appropriate test formats significantly affects the validity and reliability of assessment results. This article aims to comprehensively examine various types of tests and their characteristics within the context of educational evaluation. The research method employed is a literature study analyzing scholarly journal articles and academic books relevant to educational evaluation and assessment. The findings indicate that tests in education can be classified into written tests, oral tests, and performance tests, each of which has distinct characteristics, strengths, and limitations. A thorough understanding of test types and their characteristics is expected to assist educators in designing learning evaluations that are objective, fair, and meaningful.